Post a New Question

Mathmatics

posted by .

2a+6b-3(a+3b) raised to the power of 2
solve with steps

  • Mathmatics -

    First simplify given expression
    2a+6b-3(a+3b).... first remove parentheses
    =2a+6b-3a-9b .... group like terms
    =2a-3a +6b-9b .... sum like terms
    =-a-3b
    =-(a+3b)

    Square expression
    [-(a+3b)]^2 .... ^2 means raise to 2nd power
    =(-1)^2 (a+3b)^2
    =(a+3b)^2 .... use identity (x+y)^2=x^2+2xy+y^2
    =a^2+6b+9b^2

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question